2021
DOI: 10.1002/pro.4083
|View full text |Cite
|
Sign up to set email alerts
|

Human DND1‐RRM2 forms a non‐canonical domain swapped dimer

Abstract: RNA recognition motif (RRM) being the most abundant RNA binding domain in eukaryotes, is a major player in cellular regulation. Several variations in the canonical βαββαβ topology have been observed. We have determined the 2.3 Å crystal structure of the human DND1-RRM2 domain. The structure revealed an interesting non-canonical RRM fold, which is maintained by the formation of a 3D domain swapped dimer between β 1 and β 4 strands across protomers.We have delineated the structural basis of the stable domain swa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Whether the different reported functions of DND1 are species-specific also remains to be clarified. A recent study revealed an interesting 3D domain swapped dimerization of the DND1-RRM2 domain [40], which increases surface area for multimeric interactions and may allow DND1 to exert different functions in different context. Further investigations are warranted to elucidate the mechanisms and causes underlying the multifaceted roles of DND1.…”
Section: Other Molecular Functions Of Dnd1mentioning
confidence: 99%
“…Whether the different reported functions of DND1 are species-specific also remains to be clarified. A recent study revealed an interesting 3D domain swapped dimerization of the DND1-RRM2 domain [40], which increases surface area for multimeric interactions and may allow DND1 to exert different functions in different context. Further investigations are warranted to elucidate the mechanisms and causes underlying the multifaceted roles of DND1.…”
Section: Other Molecular Functions Of Dnd1mentioning
confidence: 99%